2015
DOI: 10.4236/oju.2015.511032
|View full text |Cite
|
Sign up to set email alerts
|

Urolithiasis: Diagnostic and Therapeutic Aspects in Urology Department of N’Djamena in Chad

Abstract: Introduction: To study the clinical, paraclinical, diagnostic aspects and manage patients with urolithiasis according to the available technical facilities in urology department of N'Djamena in Chad. Urolithiasis is defined as the presence of one or more stony concretions located at any level of a segment of the urinary tract: calyx, renal pelvis, ureters, bladder and urethra. Materials and Methods: This was a descriptive type of a prospective study over a period of 4 years, from January 2008 to December 2011,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…22 Authors reported flank pain, hematuria and dysuria as the main presenting symptoms of urolithiasis, which is also the case in our study. [2][3][4]12,14,25,30 Apart from this, a study conducted by Odzebe et al and Rimtebaye et al found a high rate of acute urinary retention in their review (26.5% and 28.7%). 3,21 This variation can be explained by the high incidence of lower tract stone and obstructive conditions in their patients.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…22 Authors reported flank pain, hematuria and dysuria as the main presenting symptoms of urolithiasis, which is also the case in our study. [2][3][4]12,14,25,30 Apart from this, a study conducted by Odzebe et al and Rimtebaye et al found a high rate of acute urinary retention in their review (26.5% and 28.7%). 3,21 This variation can be explained by the high incidence of lower tract stone and obstructive conditions in their patients.…”
Section: Discussionmentioning
confidence: 91%
“…11,[25][26][27] Furthermore, reports from other countries recognized urolithiasis among the major reasons of urologic surgical admission. 2,3,14 Worldwide, the estimated male to female ratio of urolithiasis ranges from 1.5 to 2.5:1. 7 Comparable with this, our study and others also confirmed urolithiasis as a male predominant disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect is marked in higher income countries, but is attenuated in lower-middle income countries 8 10. This may be attributable to lack of availability of prompt intervention in developing countries, leading to later presentation and invasive treatments including nephrectomy 59–61. Following surgical treatment, management to prevent recurrence is recommended,13 again this may not be available in developing countries.…”
Section: Discussionmentioning
confidence: 99%